Adopt a Startup (HIS-E) model: An example of education for sustainable humane entrepreneurship despite COVID-19. Issue 2 (3rd April 2022) - Robles, Sylvia Azucena
ABSTRACT: Adopt a Startup (AaS-Up), a Humane-Innovation-Sustainable-based Entrepreneurship (HIS-E) model, has been the link between entrepreneurship in the classroom and the "real world" while empowering under-represented startups and students. Research confirms that entrepreneurship and innovation have been recognized as critical drivers of sustainable economic development and competitive advantage. During the Pandemic, the HIS-E was one of the few programs that continued to assist the local startups and develop an entrepreneurial mindset. HIS-E maintained quality and innovative entrepreneurship education and community outreach by transitioning to a virtual platform of collaboration. Indeed, some of these quality entrepreneurship practice components include experiential learning, collaboration across disciplines, and the infusion of sustainability and innovation into the curriculum. Finally, I address important implications, challenges, and learning outcomes for stakeholders interested in replicating this Model to stimulate entrepreneurial activity.